2020
DOI: 10.3390/agriculture10020040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Concentration of Bioactive Compounds in Garlic Cultivated from Air Bulbils

Abstract: This study was designed to determine the chemical composition, antioxidant activity, and selected bioactive compound content and occurrence in whole immature and mature garlic plants grown from air bulbils. Two winter garlic cultivars, Harnaś and Ornak, of Polish origin, were cultivated from air bulbils at the Experimental Station of the Agricultural University in Kraków, Poland. Harvest bunching of garlic of both cultivars was carried out in May and in June. Mature plants were harvested in July. In whole plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The results of the present study regarding the vitamin C content are similar to those reported by Azzini et al (2014) [21] in Italian garlic varieties, but they are superior to those reported [22,23].…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study regarding the vitamin C content are similar to those reported by Azzini et al (2014) [21] in Italian garlic varieties, but they are superior to those reported [22,23].…”
Section: Discussionsupporting
confidence: 83%
“…Following the optimization of individual compounds, the parameters of ion path were obtained, which are presented in Table 1 . The following are included among the parameters: focusing potential (FP): 200 V; collision cell entrance potential (CEP): 0 V; decluttering potential (DP): 20 V; entrance potential (EP): 10 V; collision cell exit potential (CXP): 2 V [ 25 , 26 , 27 , 28 ]. To confirm the identification of studied compounds the comparison of precursor/production pair m / z values and LC retention times with standards was performed on investigated samples.…”
Section: Methodsmentioning
confidence: 99%
“…In the last 10 years, several studies have reported that Allium contains several secondary metabolites in the bulbs, flowers and leaves [ 6 , 10 , 11 , 12 , 13 ]. Secondary metabolites are rich in health benefits because they have several bioactivities such as antioxidant, anticancer, antibacterial, antifungal, anti-inflammatory and anti-platelet [ 5 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Based on this, this review focused on the antioxidant activity found in the leaves of nine Allium species that have been extensively studied [ 27 ].…”
Section: Introductionmentioning
confidence: 99%